2008
DOI: 10.1128/aac.00909-07
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with the Selection of Mutations Conferring Resistance to Protease Inhibitors (PIs) in PI-Experienced Patients Displaying Treatment Failure on Darunavir

Abstract: The objective of this study was to characterize the mutations selected by darunavir (DRV) use in protease inhibitor (PI)-experienced patients and the associated factors. We analyzed treatment failure in 54 PIexperienced human immunodeficiency virus (HIV)-infected patients on a DRV-and ritonavir-containing regimen. Viral genotyping was carried out at the baseline, at between 1 and 3 months of treatment, and at between 3 and 6 months of treatment to search for the selection of mutations conferring resistance to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
30
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 28 publications
1
30
0
Order By: Relevance
“…Our data strengthen the observations of Lambert-Niclot et al (5), suggesting the noninvalidation of TPV susceptibility by DRV-associated mutations; in our experience, virological response to TPV benefited from the presence of L76V. In this respect, we agree with Lambert-Niclot et al, who stated that TPV may remain active after DRV use and that its presence could be useful to construct an optimal salvage regimen in multiexperienced patients.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Our data strengthen the observations of Lambert-Niclot et al (5), suggesting the noninvalidation of TPV susceptibility by DRV-associated mutations; in our experience, virological response to TPV benefited from the presence of L76V. In this respect, we agree with Lambert-Niclot et al, who stated that TPV may remain active after DRV use and that its presence could be useful to construct an optimal salvage regimen in multiexperienced patients.…”
supporting
confidence: 79%
“…Lambert-Niclot et al (5) suggested that the virological failure of a DRV/r-based regimen was due to the selection of mutations which, although increasing the level of DRV/r, did not affect tipranavir (TPV) susceptibility; moreover, L76V was found to be protective for the development of additional DRV-associated mutations. L76V has also been reported to increase TPV susceptibility (8,9); nevertheless, the real clinical implication of this mutation in response to TPV-containing regimens is still unknown.…”
mentioning
confidence: 99%
“…The most common mutations identified were V32I, L33F, I54M/L, I84V, and L89V (17,21). In the present study, HIV-1 variants resistant to DRV, which replicated in the presence of 1 and 5 M DRV, emerged by passages 39 and 51, respectively.…”
Section: Discussionmentioning
confidence: 68%
“…The use of inconsistent methods between studies associating PR genotype with clinical response or in vitro susceptibility can result in confusing or even misleading interpretation guidelines. Treatment with lopinavir (1,11,12,23,26,27), darunavir (19), or other PIs (5,7,29) can lead to selection of the L76V mutation. L76V is associated with reduced response to darunavir (13).…”
mentioning
confidence: 99%